PROBLEMATIC ISSUES OF PREVENTION OF ALCOHOL CONSUMPTION BY PERSONS DRIVING VEHICLES - LENSKY V.M.; KOCHKAREV A.I. (Legal Bulletin)
The article discusses various ways to prevent intoxicated persons from driving vehicles, and makes proposals to consolidate such measures in the domestic legal system. The relevance of the article is due to the attention being drawn to the category of «sober driver» and insufficient legal regulation of preventive measures aimed at suppressing driving under the influence of alcohol. The main goal is the establishment and legislative regulation of preventive measures to prevent the driver from using a vehicle under the influence of alcohol. The problems under consideration are the lack of comprehensive consolidation in the legislation of the Russian Federation of preventive measures to prevent driving under the influence of alcohol. The methods used. In the article, along with general scientific methods, comparative legal, formal logical, and other approaches were used. The novelty of the scientific work lies in the conclusions recommended by the authors and specific proposals for improving administrative legislation.